2010
DOI: 10.1016/j.jtcvs.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

New clinically applicable method for visualizing adjacent lung segments using an infrared thoracoscopy system

Abstract: Infrared thoracoscopy with indocyanine green makes it possible to identify the target lung segment easily and quickly without the need for inflation. This method will be especially useful for cases associated with severe emphysema or when surgery offers a limited view, as is the case with video-assisted thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 12 publications
0
120
0
5
Order By: Relevance
“…According to other toxicity studies, intravenous injection of up to 5.0 mg/kg ICG is quite safe and acceptable (9). In the present study, the sensitivity of this ICG system was better than that of previous reports, so we were able to create ICGF images twice in one operation (8,10). For example, when we performed right segments (S)9+10 segmentectomy, we first divided the intersegmental line between S6 and the basal segments along the ICGF demarcation after clamping the pulmonary artery of S6.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…According to other toxicity studies, intravenous injection of up to 5.0 mg/kg ICG is quite safe and acceptable (9). In the present study, the sensitivity of this ICG system was better than that of previous reports, so we were able to create ICGF images twice in one operation (8,10). For example, when we performed right segments (S)9+10 segmentectomy, we first divided the intersegmental line between S6 and the basal segments along the ICGF demarcation after clamping the pulmonary artery of S6.…”
Section: Resultsmentioning
confidence: 75%
“…In their study, the dominant pulmonary artery of the target segment (TS) was ligated, and after injection of ICG, infrared thoracoscopy revealed ICGF. Their detailed macroscopic and microscopic study confirmed that the demarcation corresponded to the intersegmental line (7,8).…”
Section: Summary Of Icg Fluorescencementioning
confidence: 79%
See 1 more Smart Citation
“…The technique of visualizing the demarcation line based on fluorescence imaging with indocyanine green (ICG) during thoracotomy or thoracoscopy was recently developed and used by surgeons, with relatively high success rates (3,5). From our experiences during anatomical segmentectomy by TS, we noticed that ICG brightness varied in every case, depending on the blood flow or presence of anthracosis; therefore, there is a doubt on the accuracy of ICG fluorescence imaging in demarcating the segmental plane.…”
Section: Original Articlementioning
confidence: 99%
“…In the latter cases, depiction of the inflation-deflation line is difficult when air is poorly sent from the segmental bronchus planned for resection. Problems encountered in cases of emphysema include: (I) inaccurate border due to communication with the resected segments arising from peripheral lung destruction; and (II) difficulty in inducing collapse due to air trapping.Aside from the air-sending method for visualizing the intersegmental plane, other methods are available, including a method involving injection of indocyanine green (ICG) into the segmental bronchus planned for resection (20,21) and a method in which the intersegmental line is observed under an infrared thoracoscope after intravenous injection of ICG following pulmonary artery blocking (22,23). The method involving ICG injection into the bronchus involves the risk for failure to achieve uniform dispersion of the dye in subsegments.…”
mentioning
confidence: 99%